A History of the Idea of Speaking into the Air: A Conversation with John Durham Peters - John Durham Peters; Chris Russill; Hannah Dick; Liam Cole Young (Media Theory, 2022)
The following is a conversation that took place between John Durham Peters (JDP) and the editors of this special issue, Chris Russill (CR), Hannah Dick (HD), and Liam Cole Young (LCY) on November 18, 2021. The conversation transcript has been edited for clarity.